Strategi Komunikasi Guru Dalam Meningkatkan Minat Belajar Siswa Di Era Digital - Mudiasih, Asri; Anaqo, Wafiq; Febriany, Febriany (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2024)
In today's digital age, the challenge in education is how teachers can effectively communicate learning materials so as to increase students' interest in learning. students. This research aims to identify and analyze communication strategies used by teachers in an effort to increase students' interest in learning. in the digital era at SD N 4 Pejagoan. Qualitative research methods were used by conducting in-depth interviews withinterviews with a number of experienced teachers. The results of the analysis showthat effective communication strategies involve the use of information technology, digital learning applications, and a personalized approach in the interaction between teachers and students. interaction between teachers and students. The implications of this research are the importance of developing digital communication competencies for teachers as well asutilization of technology as a tool to stimulate students' interest in learning in the context of today's increasingly digitized education.